Pembelajaran Menyimak Cerita Fantasi Menggunakan Media Film Kartun Pada Siswa Kelas VII Di SMP Plus Ja-Alhaq Kota Bengkulu - Setiawati, Arni (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This study aims to identify the steps involved in listening to fantasy story lessons using cartoon film media. The method used is descriptive qualitative with a field research approach. Data collection techniques were conducted through interviews, observations, and documentation. The results of the study show that there are three stages in the listening to fantasy story lessons using cartoon film media: the planning stage, the implementation stage, and the closing stage. In conclusion, the use of cartoon film media can assist teachers in carrying out the lessons. This media attracts students' interest and helps them in understanding the material, especially in listening to fantasy story lessons. However, there are supporting factors such as adequate facilities and enthusiastic students, and inhibiting factors such as difficulties in managing the students. Keywords: Supporting Factors, Inhibiting Factors, Cartoon Film Media, Listening to Fantasy Stories